A conceptual model of “University of the Future” for enhancing job opportunities in Bandung, Indonesia through humanizing education - Suseto, Ramdhan; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
This paper offers a conceptual business model of a Malaysian-based University of the Future, called MyUni, with one of its value proposition in engaging and transforming local and global communities. Globally, labor productivity and unemployment has increased to crisis levels. However, the global economy is growing at a slower rate. Increasing employment opportunities is a must, particularly for young people. This is because, fresh graduates are facing difficulties in finding jobs if they do not have the required skill and competency. The United Nations SDGs (Sustainable Development Goals) is a guideline to provide a shared blueprint for peace and prosperity for the people and the planet. This paper uses the design and system thinking methodology to understand the main problems and propose a business model of University of the Future (UotF) for MyUni in providing humanizing entrepreneurship education to the youth in Bandung, Indonesia. The contribution of this paper is a conceptual and validated business model in BMC and VPC format. The UotF business model for MyUni proposed in this paper will help youth in Bandung, Indonesia to gain the basic knowledge, skills and human values in contributing to the wellbeing and development of the community.